Improvement of Numeracy Skills of Grade VI Students at SDNCiherang 02 Through A Game-Based Tutoring Program - Sintia Ardana; Fransisca Iriani Roesmala Dewi; Zahro Zulryanti Zulryanti; Tantony Winata; ⁠⁠Anazwa Najmicitta Nurzaman; Jane Louis (Universitas AMIKOM Yogyakarta, 2026)
Low numeracy skills among elementary school students pose a significant challenge for academic readiness, particularly in facing the Academic Competency Test (TKA) scheduled for 2026. This community service program aimed to improve literacy and numeracy skills of sixth-grade students at SDN Ciherang 02, Pacet District, Cianjur Regency through a game-based learning approach. Prior to implementation, the mean Mathematics score was 43.52 and Indonesian language score was 67.00. The program was implemented over 8 days through seven interactive activities, involving 27 sixth-grade students as participants. Academic competency was measured using TKA-format test items consisting of 30 Indonesian language and 20 Mathematics multiple-choice items, administered as pre-test and post-test. Data were analyzed using Paired Samples t-test after normality was confirmed via Shapiro-Wilk test. Results showed that Mathematics scores improved significantly from 43.52 to 56.11 (t = -4.301, p < 0.001, d = -0.828), while Indonesian language scores showed a non-significant improvement from 67.00 to 68.70 (t = -0.870, p = 0.392, d = -0.167). Interview findings revealed that students found TKA-format reading items challenging due to limited daily reading habits. This program is recommended as a replicable school-based game-based learning model for TKA preparation.